Risk of metachronous advanced neoplasia in patients with multiple diminutive adenomas - Kim, Jung Yoon; Kim, Tae Jun; Baek, Sun Young; Ahn, Soohyun; Kim, Eun Ran; Hong, Sung Noh; Chang, Dong Kyung; Kim, Young Ho (American Journal of Gastroenterology, 2018)
Objectives: Individuals with advanced adenomas or three or more adenomas have a higher risk of metachronous advanced neoplasia (AN) and are recommended to undergo surveillance colonoscopy at shorter intervals. However, it is questionable whether patients with multiple (three or more) non-advanced diminutive adenomas should be considered as high-risk. Methods: We analyzed 5482 patients diagnosed with one or more adenomas during their first colonoscopy screening and who underwent a follow-up colonoscopy. Patients were categorized into four groups based on adenoma characteristics at baseline: Group 1, 1-2 non-advanced adenomas; Group 2, ≥3 non-advanced, diminutive (1 to 5 mm) adenomas; Group 3, ≥3 non-advanced, small (6-9 mm) adenomas; and Group 4, advanced adenomas. Results: During a median follow-up of 38 months, the incidence of metachronous AN at surveillance colonoscopy was 5.6%. The incidence of AN was 3.9% in group 1, 5.9% in group 2, 10.6% in group 3, and 22.1% in group 4. The adjusted hazard ratios (HRs) [95% confidence intervals (CIs)] for metachronous AN between group 2, group 3, and group 4, and low risk group 1 were 1.71 (0.99- 2.94), 2.76 (1.72-4.44), and 5.23 (3.57-7.68), respectively. Compared with group 4, the adjusted HRs (95% CIs) for group 1, group 2, and group 3 were 0.19 (0.13-0.28), 0.32 (0.18-0.59), and 0.52 (0.31-0.89), respectively. Conclusions: We found that patients with three or more non-advanced diminutive adenomas had a borderline increased risk of metachronous AN compared with patients with low risk adenomas.
Keywords: Adenoma; Aged; Colonic Polyps; Colonoscopy; Colorectal Neoplasms; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Neoplasm Staging; Neoplasms, Second Primary; Practice Guidelines as Topic; Proportional Hazards Models; Republic of Korea; Retrospective Studies; Risk Assessment; Risk Factors; Time Factors; Tumor Burden